2014
DOI: 10.1186/s12951-014-0054-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of size–dependent cell adhesion on nanostructured interfaces

Abstract: BackgroundCells explore the surfaces of materials through membrane-bound receptors, such as the integrins, and use them to interact with extracellular matrix molecules adsorbed on the substrate surfaces, resulting in the formation of focal adhesions. With recent advances in nanotechnology, biosensors and bioelectronics are being fabricated with ever decreasing feature sizes. The performances of these devices depend on how cells interact with nanostructures on the device surfaces. However, the behavior of cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 41 publications
4
59
0
Order By: Relevance
“…Furthermore the mixed pillar arrays will likely be useful tools to dissect differences in adhesion behaviour in large mammalian cells that are grown on top of the pillars. [38] Using the mixed pillar array we were able to determine the preferential pillar size for Plasmodium sporozoites association. We found that sporozoites tend to associate better with pillars of the size of blood capillaries in the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the mixed pillar arrays will likely be useful tools to dissect differences in adhesion behaviour in large mammalian cells that are grown on top of the pillars. [38] Using the mixed pillar array we were able to determine the preferential pillar size for Plasmodium sporozoites association. We found that sporozoites tend to associate better with pillars of the size of blood capillaries in the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…29 For example, nanosphere lithography has been reported to fabricate nanohole arrays to be used as replication molds for the casting of polymer pillars. 30 These structures have already been exploited for the development of smart surfaces thanks to their peculiar wetting behavior, e.g. to allow easier harvesting of cultured cells.…”
Section: Coupling Remote Photocatalysis With Nanosphere Lithographymentioning
confidence: 99%
“…The performances of such biodevices depend on how cells interact with nanostructures on the chip surfaces, in some cases, changing drastically adhesion properties and biocompatibility. Surface properties in micro‐ and nanodevices are of huge importance in biomedical applications …”
Section: Introductionmentioning
confidence: 99%
“…Surface properties in micro-and nanodevices are of huge importance in biomedical applications. [23,26,27] It is, therefore, crucial to push technological limits further and study the effects of process parameters yielding ultrahigh aspect ratio nanopillars, controlling etch angle and sidewall roughness. In this respect, our motivation is to use the Bosch process and pseudo-Bosch process etching in an inductive-coupled plasmadeep reactive ion etching (ICP-DRIE) reactor to obtain highquality manufacturing and to push limits further as far as nanopillar length is concerned.…”
Section: Introductionmentioning
confidence: 99%